Report of the Joint Workshop on Induced Special Regions. (November 2019) - Meyer, Michael; Bakermans, Corien; Beaty, David; Bernard, Douglas; Boston, Penelope; Chevrier, Vincent; Conley, Catharine; Feustel, Ingrid; Gough, Raina; Glotch, Timothy; Hays, Lindsay; Junge, Karen; et al.
Abstract: The Joint Workshop on Induced Special Regions convened scientists and planetary protection experts to assess the potential of inducing special regions through lander or rover activity. An Induced Special Region is defined as a place where the presence of the spacecraft could induce water activity and temperature to be sufficiently high and persist for long enough to plausibly harbor life. The questions the workshop participants addressed were: (1) What is a safe stand-off distance, or formula to derive a safe distance, to a purported special region? (2) Questions about RTGs (Radioisotope Thermoelectric Generator), other heat sources, and their ability to induce special regions. (3) Is it possible to have an infected area on Mars that does not contaminate the rest of Mars? The workshop participants reached a general consensus addressing the posed questions, in summary: (1) While a spacecraft on the surface of Mars may not be able to explore a special region during the prime mission, the safe stand-off distance would decrease with time because the sterilizing environment, that is the martian surface would progressively clean the exposed surfaces. However, the analysis supporting such an exploration should ensure that the risk to exposing interior portions of the spacecraft (i.e., essentially unsterilized) to the martian surface is minimized. (2) An RTG at the surface of Mars would not create a Special Region but the short-term result depends on kinetics of melting, freezing, deliquescence, and desiccation. While a buried RTG could induce a Special Region, it would not pose a long-term contamination threat to Mars, with the possible exception of a migrating RTG in an icy deposit. (3) Induced Special Regions can allow microbial replication to occur (by definition), but such replication at the surface is unlikely to globally contaminate Mars. An induced subsurface Special Region would be isolated and microbial transport away from subsurface site is highly improbable.